Serosurvey of Selected Zoonotic Pathogens in Polar Bears (Ursus maritimus Phipps, 1774) in the Russian Arctic - Alexander Yu. Alekseev; Andrei N. Boltunov; Anastasiya A. Derko; Kirill A. Sharshov; Lyubov S. Adamenko; Alexander M. Shestopalov (Diversity, 2022)
Antibodies to several pathogens were detected in the serum samples of nine polar bears (Ursus maritimus, Phipps, 1774) from areas of the Russian Arctic. Plasma was studied for antibodies to sixteen infectious and parasitic diseases using indirect Protein-A ELISA. It is known that when using ELISA, the interaction of antibodies with a heterologous antigen is possible due to immunological crossings between antigens. We investigated the plasma for the presence of antibodies to the major pathogens and for the presence of antibodies to pathogens, for which the cross-immunological reactions to these pathogens are described. For example, antibodies to the pathogens of opisthorchiasis, clonorchiasis, and ascariasis were found simultaneously in four polar bears. Antibodies to both anisakidosis and trichinellosis pathogens were found in six animals. The data obtained may also indicate a joint invasion by these pathogens. Unfortunately, due to the small number of animals sampled, it is impossible to carry out statistical processing of the data.